Asynchronous interaction and discursive resources for knowledge construction in times of pandemic - Castellanos Ramírez, Juan Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this work, forms of asynchronous interaction developed by university students during the Covid-19 pandemic are identified. Through a case study, the structure of participation and the discursive mechanisms used by four groups of students were analyzed; the groups discussed different educational topics over six weeks. Due to the process of adaptation to the virtual training modality, the groups presented various difficulties in maintaining constant and productive conversations in the forums; however, a slight improvement can be seen after the third week of work when the students begin to internalize the new modality.